PENILAIAN PENGELOLAAN SISTEM PERTANIAN BERKELANJUTAN PADA SKALA USAHA TANI - Samekto, Riyo - (Innofarm:Jurnal Inovasi Pertanian, 2011)
Abstracts The main cause of confusion is people’s perception of what constitutes ‘agriculture’ and ‘sustainability’. The attributes of agriculture range from specific soil-plant interactions at the field level, to international trading arrangements at the global level. Despite the diversity in conceptualizing, there is some broad consistency among definitions. Definitions generally contain three important criteria (Pesek, 1994): (a) environmental quality and ecological soundness; (b) plant and animal productivity; and, (c) socio-economic viability. The definition makes scale of sustainability assessment  influencing the indicators selected. The purpose of the paper is to discuss agricultural sustainability at farm scale and to propose the way to measure management of sustainable agricultural system at farm scale as a complement for biophysical land survey. The indicators of sustainability selected should include indicators at the three requirements of agricultural sustainability. As consequency of using indices, it is suggested to union biophysical survey to measurement agricultural sustainabity in order to provide reasons that is undetected by indices way of measurement. Key words: sustainable agricultural system, agricultural sustainability, farm scale, indicator agricultural sustainability, sustainability indices.